Males Resemble Females: Re-Evaluating Sexual Dimorphism in Protoceratops andrewsi (Neoceratopsia, Protoceratopsidae) - Maiorino, Leonardo; Farke, Andrew A.; Kotsakis, Tassos; Piras, Paolo (PLOS ONE, 2015)
Background Protoceratops andrewsi (Neoceratopsia, Protoceratopsidae) is a well-known dinosaur from the Upper Cretaceous of Mongolia. Some previous workers hypothesized sexual dimorphism in the cranial shape of this taxon, using qualitative and quantitative observations. In particular, width and height of the frill as well as the development of a nasal horn have been hypothesized as potentially sexually dimorphic. Methodology/Principal Findings Here, we reassess potential sexual dimorphism in skulls of Protoceratops andrewsi by applying two-dimensional geometric morphometrics to 29 skulls in lateral and dorsal views. Principal Component Analyses and nonparametric MANOVAs recover no clear separation between hypothetical “males” and “females” within the overall morphospace. Males and females thus possess similar overall cranial morphologies. No differences in size between “males” and “females” are recovered using nonparametric ANOVAs. Conclusions/Significance Sexual dimorphism within Protoceratops andrewsi is not strongly supported by our results, as previously proposed by several authors. Anatomical traits such as height and width of the frill, and skull size thus may not be sexually dimorphic. Based on PCA for a data set focusing on the rostrum and associated ANOVA results, nasal horn height is the only feature with potential dimorphism. As a whole, most purported dimorphic variation is probably primarily the result of ontogenetic cranial shape changes as well as intraspecific cranial variation independent of sex.